PMP Practice Makes Perfect : Over 1000 PMP Practice Questions and Answers. - Estrella, John (John Wiley & Sons, 2011)
A unique learning resource to prepare for the PMP certification examWithout sufficient practice and preparation for taking the Project Management Institute's (PMI's) PMP certification exam, you won't be able to actually put your skills into practice in the real world! To help you achieve your goal of passing the exam, this two-part prep book covers all elements of the brand-new Project Management Professional exam. A team of experts presents you with a solid overview of the exam as well as hundreds of questions, detailed answers, and explanations. In addition, each question is accompanied by c.